Chromatography-free, Mitsunobu-triggered heterocyclizations of salicylhydroxamic acids to 3-hydroxybenzisoxazoles. Issue 48 (30th November 2016) - Van Eker, Daniel; Chauhan, Jay; Murphy, William A.; Conlon, Ivie L.; Fletcher, Steven
Graphical abstract: Highlights: 3-Hydroxyisoxazoles are prepared rapidly from salicylhydroxamic acids. Chromatography-free Mitsunobu reactions. The chemistry is mild and efficient, tolerating a wide range of functional groups. Abstract: The Mitsunobu reaction has become one of the most powerful tools to alkylate acidic pronucleophiles. A significant caveat of Mitsunobu chemistry, however, is that the reaction mixture is often plagued with purification problems owing to the phosphine oxide and hydrazine dicarboxylate by-products. In addition to the development of more readily separable Mitsunobu reagents, the product's physicochemical properties may be exploited to facilitate purification. In this regard, we present a swift and efficient preparation of 3-hydroxybenzisoxazoles by the Mitsunobu-triggered heterocyclizations of salicylhydroxamic acids, which can be isolated by an acid–base work-up. As expected, a range of functional groups was compatible with the chemistry.